The sharpshooter : brimstone and gold fever - Cole, Tobias (Cole, Tobias. Sharpshooter, 2019)
Brimstone: "The story of Andersonville prison camp was written in blood, with few left alive to tell it. Union Army sharpshooter Jed Wells was one of them, a man of conscience sworn to share the tales of those who suffered and died beside him. It is a promise that has brought Jed to Kansas and to small-town sheriff Amos Broughton, a friend and fellow survivor of hell on earth. But the ghosts that haunt Broughton are demanding and hungry. And his dangerous obsession with a mysterious man of God threatens to explode in a vengeful rain of bullets and death -- forcing Jed Wells to take up his rifle once again to save a soul damned by terrible secrets buried with the bones of captured soldiers in the Georgia mud"--FantasticFiction.com.